Creating Digital Creativepreneur for SMEs in Rural Indonesia - Rukmana, Otong; ., Djamaludin; Achiraeniwati, Eri; As’ad, Nur Rahman; Sri Rejeki, Yanti (KnE Social Sciences, 2023)
SMEs in Balida Village, Majalengka, strives to survive and grow in the pandemic era, while digitalization era provides opportunities to be more creative and reach a broader market efficiently. Main problem is lack of digital literacy and skill among them. Those weaknesses and opportunities drive to a solution program of a digital creative entrepreneur development that aims to enhance digital literacy and accelerate digital transformation in SMEs sector. The program applied activities in current analysis, design solution, training, assistance, and evaluation. The main activities are training and assistance for implementing of digital marketing through a marketplace platform to 32 SMEs with various business fields, such as food and culinary, convection and fashion, groceries, art, health and beauty, and services. The evaluation showed that training and technical assistance had increased digital literacy and interest in digital marketing of SMEs. They plan to expand the market and sell products using the marketplace platform. At the end of this 7-month program, 5 digital creative entrepreneurs were born with the need for advanced development programs. Keywords: digital literacy, digital creative entrepreneur, digital marketing, marketplace